B08 The effect of the goal kick rule change on the team’s performance in ball possession and goal scoring in elite male football - Torkornoo, Benjamin (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Goalkeepers have always played an important role Defensively. Due to rule changes and tactical transitions, goalkeepers now also have an influence on attacking aspects of the game (Szwarc et al., 2023, Baltic J Health Phys Act). The most recent rule change allows attacking players in the box during goal kicks, which creates extra space for the attacking team at the time of the goal kick without direct pressure from the opponent. This is beneficial for teams in the build-up who try to increase space to create goal scoring opportunities in advantageous positions eventually high up the pitch (Goes et al., 2019, Big Data, 7, 57-70). This latest rule change gives the attacking team an extra 640 m2 of space to displace the opposition defence in deeper positions to create scoring opportunities. As of date, no research has looked at the goal kick rule change and its effect on the distribution tendencies and tactical approaches implemented, when attempting to progress the ball up the field from a goal kick. This research aims to analyse the distribution tendencies of Premier League teams in the 2022/2023 season and compare goal kick and build-up behaviour between teams, depending on their finishing position in the season. A secondary data analysis will be conducted on Premier League matches during the 2022/2023 season, including 2136 goal kick sequences cropped from 760 games. The location of the first pass of the goal kick, number of passes during the build-up, duration of the build-up phase, and the amount of goalkeeper touches after the initial goal kick will be analysed. Additionally, the outcome of successful goal kicks will be analysed considering the action and location of the action. All data analysis will be done using HUDL Sportscode (v12.29.0., Hudl, USA). Statistical analysis will evaluate the effect of team’s league table position on the start of the goal kick, build up phase, and the outcome of the goal kick.